(untitled) (Islamic Sciences Journal, 2023)
The semantic study is one of the studies that deal with the meaning, as it includes considering the syntactical and grammatical formulas in order to determine the meaning of actions directed by the hypocrites against the believers, which are mentioned in the context of the verses of the Noble Quran. The present tense was chosen as an example for this type of work because it signifies renewal and occurrence indicating the constant or renewed intentions of the hypocrites in order to suppress the Islamic call. The research included an introduction and two requirements, the first of which included the definition of signification, action and hypocrisy in language and convention, and the second section analyzed the verses concerned with the lesson. The research ended with a conclusion that indicate the most important results shown in a table the contains verses with the verbs that are intended in the current research.